Reopening the country: Recommendations for nuclear medicine departments - Sanaz Katal; Saif Azam; Emilio Bombardieri; Maria Picchio; Ali Gholamrezanezhad (World Journal of Nuclear Medicine)
The best practices for nuclear medicine departments to operate safely during the COVID-19 pandemic have been debated in the literature recently. However, as many governments have started to ease restrictions in activity due to COVID-19, a set of guidelines is needed to resume routine patient care throughout the world. The nonessential or elective procedures which were previously postponed or canceled during the COVID-19 pandemic will gradually restart in the following weeks despite the continued risks. In this paper, we aim to review some of the most effective general precautions to restart the regular nuclear medicine operations safely.